THE PHYSIOLOGY OF THE NERVOUS SYSTEM: FUNCTIONAL MECHANISMS AND NEURAL COMMUNICATION (Ustozlar uchun, 2025)
The nervous system is a highly complex network responsible for the coordination of all physiological functions in the human body. It integrates sensory input, processes information, and initiates motor output. This paper explores the physiological mechanisms underlying neural activity, with particular emphasis on the structure and function of neurons, synaptic transmission, and the role of neurotransmitters in communication. Using data from recent neurophysiological studies, the article outlines how electrical and chemical processes form the foundation of human cognition, reflexes, and homeostasis.